The effects of weight class athletes’ nutrient consumptions and eating habits on their depression-anxiety-stress levels - Yüceloğlu Keskin, Deniz Özge; Kabadayı, Menderes; Bostancı, Özgür; Bayram, Levent; Derebaşı, Deniz Günay (Progress in Nutrition, 2020)
Diet is important in sports in terms of having an influence on bodily and mental health besidessportive performance. The objective of this study is to find out the effects of dietary habits and eating attitudeson moods of weight class athletes. The study was conducted with a total of 60 athletes -33 wrestlerswho participated in Turkey Men’s Greco-Roman Wrestling National Team Preparation Camp, 18 wrestlerswho participated in Turkey Men’s Freestyle National Team Preparation Camp and 9 judokas who participatedin Turkey Men’s Judo National Team Preparation Camp during the years 2013 and 2014. Athletes’ demographiccharacteristics and information about their three-day eating habits were found, eating attitudes test(EAT) and Depression, Anxiety and Stress Scales (DASS-42) were applied and some of their anthropometricmeasurements were found. Student-t, Mann Whitney U, Anova and Kruskal tests were used for the statisticalanalysis of data. Statistically significant difference was found between the EAT scores of Greco-romanwrestlers and freestyle wrestlers and EAT scores of Greco-roman wrestlers were found to be higher (p